1. J

    How to rewrite these formulas in the opposite form?

    I want to know how I can write from some predicate formula its negative form. For example ∀x∃y(x R y) then not(∀x∃y(x R y)) is equal to ∃x,not ∃y(x R y)))(not exist y) How do these formula work with conjunction implication and disjunction? Bellow are examples of some formulas but...
  2. A

    Rewrite an expression in a specific form

    I have an expression that looks as follows: n + (a*x+b)^c. Where 'a', 'b', 'n', and 'c' are constant numbers. The ranges of the parameters are: n = [0,0.2] a = [0.5,1.5] b = [-0.5,0.5] c = [0.5,1.5] x = [0,0.6] I would like rewrite this expression such that it will look as follows...
  3. K

    First time thread! V=4/3 . PI . R^3 Rewrite as R=....

    Hello Peeps, this is my first time posting. My name is Kees I'm 23 years old and Im from Holland. I am a carpenter atm but will start my education to be a construction supervisor which will take 4 years. Recently I started taking math classes and just got my fist grade 7.4! (out of 10) So...
  4. P

    Rewrite a function to get c*

    I've got the following function: (c*/c)*(ProfitD - c*) + (1 -(c*/c))*(ProfitM - c*)=0 I need to derive c* as a function of the other parameters. Furthermore, I know the answer should be: c*= (c * ProfitM) / (c + ProfitM - ProfitD) However, I'm not able to solve c* by myself. I do not know...
  5. P

    Rewrite multiplication of quotient.

    I'm not sure how I should rewrite this. n(n-1) * (1/n - 1/n+1) So I think n(n-1) = n^2 -n and (1/n - 1/n+1) = 1/n+1 But I'm not sure. I've got n-1/n+1 as my final answer, but are my intermediate steps right? How should I proceed?
  6. K

    Multiplication rewritten as a sum, can I rewrite division?

    Hello there: 6*2 = 2+2+2+2+2+2 I always thought of division as being somewhat the opposite of multiplication. Is it possible to rewrite \frac{6}{2} in a similar way? Thank you for your time. Kind regards, Marius
  7. K

    Rewrite polynomial*2x as a sum of polynomial

    Hello there, I have a polynomial Pn(x) multiplied by 2x: P_n(x)\, \cdot\, 2x. I want to rewrite it as a sum like this: \underbrace{P_n(x) + P_n(x) + ... + P_n(x)}_{\text{added 2\, \cdot\, x times} I realize I can do this at least one way: \sum_{i = 1}^{2x}P_n(x). However, I want to know if...
  8. D


    Hello guys I need to solve an easy derivative but I think I need to re-write my function.The function is f(x)=sin2x,is it correct if I re-write the function as f(x)=sinx+x?Thank you for your time.
  9. M

    How to rewrite this totient summation in terms of Mertens?

    The totient sum function has an identity: \displaystyle\sum_{k=1}^{N}\varphi(k) = \sum_{k=1}^N {\rm M}(\lfloor\frac{N}{k}\rfloor)k \varphi(k) is the Euler totient function, and M is the Mertens function \displaystyle M(N)=\sum_{k=1}^N \mu (k) where \mu is the Moebius function. My question...
  10. F

    Rewrite variable in given constants and variables

    Hello everyone, English isn't my native language, so I hope I can make myself clear. I'm new on this forum, because I have a question. I put this topic in this subforum, but I am not sure if this is the right one. Sorry if I'm wrong. Given is some vector A(t) and t \in \{0, 1, ...\} with...
  11. M

    How to rewrite

    1/2x^-1/2 ?
  12. J

    Ways to rewrite sequence

    Hi guys, please help me with this interesting but hard problem :) : Let K denote the set of all finite binary sequences. For example, (0,1,1) and (0,0,0,0,0,1,0) are in K but (1,1,1,1,.....) is infinite so is not in K. We look at 2 special permutations of K. Let A be the permutation that...
  13. K

    Rewrite the expression as an algebraic expression in x

    sin(2sin^-1x) *Note sine^-1 is sin inverse sin2x=2sinxcosx Drawing a triangle I found side a=x b=sq root (1-x^2) and c=1 Based on the triangle, I found cos to be sq root (1-x^2) so sin2x=2*x/1*sq root (1-x^2)=2xsqroot(1-x^2) Is the answer 2xsqroot(1-x^2)